Biological Nitrogen Fixation and Cattle Production in Tropical Environments (2023)
Biological nitrogen fixation (BNF) is a critical process for maintaining soil fertility and promoting healthy soil microbiology. In tropical pastures, BNF plays a key role in influencing protein intake during grazing. To understand the importance of nitrogen-fixing bacteria to cattle production, we conducted a thorough review of several documents. Our goal was to explore the relationship between these bacteria, nitrogen, crop and livestock production, and their ecological significance. We consulted 679 documents from different search platforms, using 12 different search equations or keyword combinations. From these, we selected 86 documents, including 37 research articles, 26 review articles, 18 theses, and 5 academic books. We have clearly organized the information to demonstrate the importance of bacteria in nitrogen utilization in pastures.